Cover Feature: Elusive Dehydroalanine Derivatives with Enhanced Reactivity (ChemBioChem 10/2019). (2nd May 2019) - Aydillo, Carlos; Mazo, Nuria; Navo, Claudio D.; Jiménez‐Osés, Gonzalo
Abstract : A hungry bear is trying to catch some slippery fish from a river; this resembles the feeling of bioorganic chemists attempting the synthesis of very reactive, elusive compounds such as the cyclic dehydroalanine derivatives (4‐methylenoxazol‐5(4 H )‐ones). Non‐destructive detection techniques such as NMR spectroscopy (the fishing net) allowed us (the bear) to monitor the very fast formation and consumption of dehydroalanines (the fish) in the reaction mixture (the river) and to combine them with other chemicals such as diazocompounds and dienes (the fruits and flowers). Finally, the bear managed to cook a good dehydroalanine fish meal! Artwork by N.M. More information can be found in the communication by G. Jiménez‐Osés et al. onpage 1246 in Issue 10, 2019 (DOI:10.1002/cbic.201800758 ).